2014
DOI: 10.1016/j.colegn.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Australian health professions student use of social media

Abstract: Increased bandwidth, broadband network availability and improved functionality have enhanced the accessibility and attractiveness of social media. The use of the internet by higher education students has markedly increased. Social media are already used widely across the health sector but little is currently known of the use of social media by health profession students in Australia. A cross-sectional study was undertaken to explore health profession students' use of social media and their media preferences fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 22 publications
0
65
1
4
Order By: Relevance
“…These include points on safeguarding patient privacy, avoiding controversial material and "pausing before posting" (BMA, 2011; Davis, 2015; Hillman and Sherbino, 2015; Parsi and Elster, 2015; Usher et al, 2014). This is in place so the students will reflect on the fact that they are posting in a public domain.…”
Section: Professionalismmentioning
confidence: 99%
See 2 more Smart Citations
“…These include points on safeguarding patient privacy, avoiding controversial material and "pausing before posting" (BMA, 2011; Davis, 2015; Hillman and Sherbino, 2015; Parsi and Elster, 2015; Usher et al, 2014). This is in place so the students will reflect on the fact that they are posting in a public domain.…”
Section: Professionalismmentioning
confidence: 99%
“…Amongst users however there were found to be some discrepancies between age groups. Usher et al (2014) found that whilst 93% of first year students used Facebook, the majority of these were aged 16-25 (97%) with only 74% of students aged 45 or over accessing the site. Facebook's influence is steadily growing with most students actively using the site.…”
Section: Facebookmentioning
confidence: 99%
See 1 more Smart Citation
“…A high proportion of healthcare professionals use social media for personal use. [5][6][7] Others consider social media, especially Facebook and Twitter, as a tool for professional development, as a means of accessing information, marketing practices and services, job opportunities, as well as sharing or adding your opinion on issues of interest to you and to other like-minded individuals online. 8,9 However, other social media research has been conducted that has implications for the profession and the patient-practitioner relationship.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is little empirical investigation documenting that there are many ethical issues that need to be considered when dealing with SNS privacy in nursing. (8) From a business viewpoint, SNSs is a useful online marketing tool because SNSs can collect personal information and can search specific target group. The marketing activities using SNS as an advertising tool promote word-of-mouth marketing.…”
Section: Introductionmentioning
confidence: 99%